A Role for Tetracycline Selection in Recent Evolution of Agriculture-Associated Clostridium difficile PCR Ribotype 078 - Kate E. Dingle (American Society for Microbiology, 2019)
ABSTRACT The increasing clinical importance of human infections (frequently severe) caused by Clostridium difficile PCR ribotype 078 (RT078) was first reported in 2008. The severity of symptoms (mortality of ≤30%) and the higher proportion of infections among community and younger patients raised concerns. Farm animals, especially pigs, have been identified as RT078 reservoirs. We aimed to understand the recent changes in RT078 epidemiology by investigating a possible role for antimicrobial selection in its recent evolutionary history. Phylogenetic analysis of international RT078 genomes (isolates from 2006 to 2014, n = 400), using time-scaled, recombination-corrected, maximum likelihood phylogenies, revealed several recent clonal expansions. A common ancestor of each expansion had independently acquired a different allele of the tetracycline resistance gene tetM. Consequently, an unusually high proportion (76.5%) of RT078 genomes were tetM positive. Multiple additional tetracycline resistance determinants were also identified (including efflux pump tet40), frequently sharing a high level of nucleotide sequence identity (up to 100%) with sequences found in the pig pathogen Streptococcus suis and in other zoonotic pathogens such as Campylobacter jejuni and Campylobacter coli. Each RT078 tetM clonal expansion lacked geographic structure, indicating rapid, recent international spread. Resistance determinants for C. difficile infection-triggering antimicrobials, including fluoroquinolones and clindamycin, were comparatively rare in RT078. Tetracyclines are used intensively in agriculture; this selective pressure, plus rapid, international spread via the food chain, may explain the increased RT078 prevalence in humans. Our work indicates that the use of antimicrobials outside the health care environment has selected for resistant organisms, and in the case of RT078, has contributed to the emergence of a human pathogen. IMPORTANCE Clostridium difficile PCR ribotype 078 (RT078) has multiple reservoirs; many are agricultural. Since 2005, this genotype has been increasingly associated with human infections in both clinical settings and the community. Investigations of RT078 whole-genome sequences revealed that tetracycline resistance had been acquired on multiple independent occasions. Phylogenetic analysis revealed a rapid, recent increase in numbers of closely related tetracycline-resistant RT078 (clonal expansions), suggesting that tetracycline selection has strongly influenced its recent evolutionary history. We demonstrate recent international spread of emergent, tetracycline-resistant RT078. A similar tetracycline-positive clonal expansion was also identified in unrelated nontoxigenic C. difficile, suggesting that this process may be widespread and may be independent of disease-causing ability. Resistance to typical C. difficile infection-associated antimicrobials (e.g., fluoroquinolones, clindamycin) occurred only sporadically within RT078. Selective pressure from tetracycline appears to be a key factor in the emergence of this human pathogen and the rapid international dissemination that followed, plausibly via the food chain.